PERANAN PEREMPUAN KOMUNITAS SURVIVOR DITINJAU DARI SEGI HUKUM ISLAM (STRATEGI FASE ERA NEW NORMAL ) - Qori Rizqiah H Kalingga (JURNAL JUSTIQA, 2021)
Law No. 22 of 1999, Law No. 25 of 1999, as well as Government Regulation No. 25 of 2000 gave enormous powers to local governments (cities and districts) to manage city / regional development, particularly in government administration and finance. The city / regency government has a very strategic role and function in the context of implementing development in all fields, which aims to increase the role of the city / district as a regional growth center, development driver, service center in all fields, as well as a center for information and innovation including in terms of technology. development. In this case, it is inseparable from the role of women as people who have an attraction for thinkers,Therefore, in this study the author will describe the role of women in the survivor community in terms of Islamic law (strategy of the new normal era phase). The outputs of this research are: providing education about that women have the right to help build family life in accordance with the applicable legal rules; familiarize oneself with learning and understanding scientific disciplines, especially those related to Islamic Law (Shari'at).